Chapter La signoria dell'ospedale di Sant'Andrea di Vercelli su Larizzate - Olivieri, Antonio (Reti Medievali E-Book, 2021)
The paper examines the case of the acquisition and management of the farm of Larizzate, near Vercelli, by the hospital of Sant'Andrea of Vercelli, in a period going from the twenties of the thirteenth century to the early fifteenth century. A comparison between the data provided by the agrarian pacts and the data made available by the periodical accounts that recorded the trend of the give and take between the owner and the dependent farmers shows the discrepancy between the services due and actually paid by the hospital employees in Larizzate. An analysis of the account books reveals, on the one hand, the great importance of the work carried out by the employees for the hospital to offset the debts accrued by the former towards the latter; on the other hand, the importance of the works for the construction and restoration of the defensive structures with which the farm was equipped. These fortifications were an expression of the lordly power exercised by the institution over the population gravitating around the farm, which can also be seen, albeit in a discontinuous manner, from other sources.